Let's face it! Young people tell us how it is - Deirdre Watson (Scottish Journal of Residential Child Care)
In 2003, Who Cares? Scotland marked its 25th year by carrying out a major consultation with young people who are currently experiencing care in Scotland. Even with recent developments (the setting up of the Care Commission, the Scottish Social Services Council and the Scottish Institute for Residential Child Care and the creation of national care standards), young people continue to report negative care experiences. It is disappointing that young people raised serious concerns in relation to many fundamental aspects of their care. The report Lets Face It! (Who Cares? Scotland, 2003) highlights a number of serious issues, such as: the lack of emotional support for young people; the need for concentrated efforts to tackle bullying; the lack of meaningful inclusion in decision making about their lives; the importance of continuing contact with family and friends; inappropriate and harsh parenting by substitute carers; and a lack of certainty about future support when they leave the care setting. These issues are not new and have been documented in a number of previous reports (Fletcher, 1993; Friday, 1998; Shaw, 1998; Who Cares? Scotland, 1997). This report highlights, however, the continuing need to address the issues raised by young people in care.